In Vitro -A Study of the Effects of Varying Interproximal Extension of Feldspathic Veneers on their Fracture Resistance - Saker, Rima; Soulieman, Haidar (Latakia University Journal -Medical Sciences Series, 2018)
. Background and objective :by going back to the history of porcelain veneers, we find the Feldspathic porcelain is one of the first materials that used in this area and emphasizes that many studies and previous research despite the availability of other ceramic materials for this purpose. These feldspathic veneers consider as a good treatment option to achieve the functional and cosmetic sides with lowest possible costs, with modest labour equipments, and trainable easily technical expertise , particularly through long-term deal in our laboratories with Feldspathic porcelain material. This study aims to study the effects of varying interproximal extension of feldspathic veneers on their fracture resistance. Materials and methods: A sample of forty upper central incisors recently extracted, and free of caries and restorations were distributed randomly to two groups. Each one has a group of 20 teeth, the first group included the numbered teeth from 1 to 20 and prepared to receive the feldspathic veneers without extension the proximal contact area while the second group included the numbered teeth from 21 to 40 and prepared with extension the proximal contact area ,all the porcelain veneers were luted with resin cement. The forces applied on them using the universal testing instrument (Test 114) with force vertically directed to the incisal edge of the veneer at a speed of 0.5 mm/min. The values of fracture resistance were recorded when the porcelain veneer was separated or cracked. Results:the mean fracture resistance force to the first group is (914.0675 N) and bigger than the mean fracture resistance force to the second group (727.9650 N). T student test showed asignificint difference between them at p≤0,05. Conclusion: The fracture resistance force of Feldspathic veneers in the first group without extension the proximal contact area is bigger than the fracture resistance of Feldspathic veneers in the second group with extension the preparation the proximal contact area. دراسة مخبرية مقارنة لتأثير إختلاف الإمتداد الملاصق للوجوه الخزفية الفلدسبارية على مقاومة إنكسارها خلفية البحث و هدفه: بالعودة إلى تاريخ الوجوه الخزفية نجد أن الخزف الفلدسباري هو من أوائل المواد التي استخدمت في هذا المجال و يؤكد على ذلك العديد من الدراسات و الأبحاث السابقة ومازالت تستخدم رغم توفر مواد خزفية أخرى لهذا الغرض. فهذه الوجوه الخزفية الفلدسبارية تعتبر خياراً علاجيا ًجيداً يحقق الناحية الوظيفية و التجميلية بأقل تكلفة ممكنة وبتجهيزات مخبرية متواضعة و خبرة فنية قابلة للتدريب و التعليم بسهولة ، لاسيما من خلال التعامل الطويل الأمد لمخابرنا مع مادة الخزف الفلدسباري. تهدف هذه الدراسة إلى دراسة تأثير اختلاف الامتداد الملاصق للوجوه الخزفية الفلدسبارية على مقاومة انكسار ها . المواد و الطرائق:تألفت عينة البحث من 40 ثنيةً علوية مقلوعة حديثاً وخالية من النخر والترميمات، تم تقسيمها عشوائيا إلى مجموعتين تحوي كل مجموعة 20سن ، تضمنت المجموعة الأولى الاسنان المرقمة من 1ال20 و حضرت لاستقبال وجوه الخزف الفلدسباري دون تجاوز التحضير لمنطقة التماس الملاصقة ، بينما شملت المجموعه الثانية الاسنان المرقمة من 21لى40 والتي حضرت لاستقبال وجوه الخزف الفلدسباري مع تجاوز التحضير لمنطقة التماس الملاصقة ، الصقت الوجوه جميعها بالاسمنت الراتنجي وطبقت عليها القوى باستخدام جهاز الاختبارات الميكانيكية العام universal testing instrument (Test 114) ، وكان اتجاه القوى عامودياً على الحد القاطع للوجه وبسرعة قص 0,5 ملم لكل دقيقة. سجلت قيم قوة مقاومة الكسر عند انفصال الوجه عن السن أو تصدعه. النتائج: بلغ متوسط قوة مقاومة الكسر للمجموعة الاولى) (914.0675 N و هو اكبر من متوسط قوة مقاومة الكسرللمجموعة الثانية و الذي بلغ) (727.9650 N.و أظهر اختبار Tستودنت وجود فروق ذات دلالة احصائية بينهما عند p≤0,05. الاستنتاج:كانت مقاومة الكسر للوجوه الخزفية الفلدسبارية في المجموعة الاولى بدون تجاوز التحضير منطقة التماس الملاصة اكبر منها في المجموعه الثانية مع تجاوز التحضير منقطه التماس الملاصقة.